Exploring the digital marketing potential and needs for digital marketing capabilities of service sector MSMEs in Thailand - Cuijten, Nachayapat; Wongpun, Sukontip; Buaprommee, Nathamon; Suwannahong, Rungsan; Inmor, Sureerut (Journal of Business Economics and Management, 2024)
The research objectives are to assess the digital marketing capabilities of micro, small, and medium-sized enterprises (MSMEs) in Thailand’s service sector, as well as to develop persona profiles for each enterprise size. The survey of 400 digital marketing personnel was conducted alongside comprehensive interviews with 10 marketing executives. The result suggests that MSMEs have moderate digital marketing skills but need to improve their knowledge in creative thinking, online consumer interaction, affiliate marketing, and change management. An executive interview emphasized issues unique to micro-enterprises, like mismatched advertising and inadequate online marketing expertise. Medium-sized enterprises have difficulties achieving online target engagement due to their inadequate SEO capabilities, whereas small enterprises struggle to effectively manage customer inquiries. The study introduces persona cards that reveal distinct competency levels and areas for improvement for each enterprise size. The research provides actionable insights for MSMEs seeking to refine their digital marketing strategies and contributes to the academic literature with understanding. Persona cards serve as a novel tool for visualizing digital marketing competencies and needs within the MSME sector.